"In the Beginning . . . ": Tools for Talking About Resuscitation and Goals of Care Early in the Admission. (November 2013) - White, Jocelyn; Fromme, Erik K.
Quality standards no longer allow physicians to delay discussing goals of care and resuscitation. We propose 2 novel strategies for discussing goals and resuscitation on admission. The first, SPAM (determine Surrogate decision maker, determine resuscitation Preferences, Assume full care, and advise them to expect More discussion especially with clinical changes), helps clinicians discover patient preferences and decision maker during routine admissions. The second, UFO-UFO (Understand what they know, Fill in knowledge gaps, ask about desired Outcomes, Understand their reasoning, discuss the spectrum Feasible Outcomes), helps patients with poor or uncertain prognosis or family–team conflict. Using a challenging case example, this article illustrates how SPAM and UFO-UFO can help clinicians have patient-centered resuscitation and goals of care discussions at the beginning of care.